Kebutuhan Air Tanaman pada Budidaya Cabai Rawit (Capsicum FrutescensL.) dengan Sistem Polybag yang Menggunakan Berbagai Tingkat Kandungan Organik Tanahh - I Made Surya Adnyana Putra; I Wayan Tika; Ida Bagus Putu Gunadnya (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2019)
The purpose of this study was to (1) determine the pattern of water needs of chili pepper (Capsicum frutescens L.) from the age of planting to flowering plants with polybag systems and (2) determine the pattern of water needs of chili pepper (Capsicum frutescens L.) with various level of soil organic content that is in line with plant age. This study used a completely randomized design consisting of five treatments and seven replications, namely treatment using 100% paddy fields, treatment using 80% paddy soil and 20% manure, 60% rice field treatment and 40% manure, soil treatment rice fields 40% and manure 60%, treatment of rice fields 20% and manure 80%. Data obtained from irrigation water needs were processed using Microsoft Excel computer programs to obtain charts and continued analysis using Analysis of Variance (ANOVA). The results of the study amount of plant water requirements in the treatment using 100% paddy soil an average of 25.29 ml / day, in the treatment of 80% of paddy field and manure 20% on average 24.26 ml / day, in the treatment of rice fields 60% and manure 40% on average 22.06 ml / day, on the treatment of rice fields 40% and manure 60% on average 21.27 ml / day, on the treatment of 20% paddy fields and manure 80% on average 19.32 ml / day. In the treatment of 20% of paddy fields and 80% of manure, water requirements are the least among the other treatments